Anti-fatigue Effect of Water Extract of Food as Medicine Compound Polygonati Rhizoma Composition on Mice - Yanxia CEN; Yucai LIANG; Jiangying ZENG; Shenggao YIN; Gailian ZHOU; Shiman CHEN (Shipin gongye ke-ji)
Objective: To investigate the anti-fatigue properties in mice of water extracts from nine different types of medicinal and edible component compositions, including Polygonati Rhizoma, Laminariae Thallus, and Rubi Fructus. Methods: A group of 10 healthy KM mice, half female and half male, were randomly assigned to each of the following groups: blank control (equal volume of distilled water), positive control (ginseng royal jelly oral liquid, 0.62 g/mL), and low, medium, and high (0.21, 0.62, 1.85 g/mL) dosage groups of water extract of compound Polygonati Rhizoma composition. The mice were gavaged continuously for 30 days and the weight data were collected during gavage. At the end of the experiment, the mice's strenuous swimming time, organ index, and serum urea nitrogen, liver, and muscle glycogen contents were examined. Results: The water extract of the compound Polygonati Rhizoma composition did not statistically differ from the blank control group in terms of the mice's weight (P>0.05), and no abnormalities were observed in the mice's organs (P>0.05). The water extract of compound Polygonati Rhizoma composition had the potential to greatly increase mouse endurance, extend their strenuous swimming time (P<0.05), lower the amount of urea nitrogen (P<0.01), and boost liver and muscle glycogen contents (P<0.01). Conclusion: Exercise tiredness is mitigated by the water extract of the compound Polygonati Rhizoma composition.